Molecular dynamics simulation of welding and joining processes: an overview - Zaenudin, M.; N. Mohammed, M.; Al-Zubaidi, Salah (International Journal of Engineering and Technology, 2018)
Molecular dynamics (MD) is a simulation of physical movements of atoms and molecules in the context of N body simulation. The atoms and molecules are allowed to interact for a period of time, giving a view of the motion of the atoms. Molecular Dynamic (MD) simulation is one of the important methods that can be applied to simulate joining processes at the atomic scale. Nowadays, many investigations had been done in molecular dynamics simulation of various joining processes like diffusion bonding, explosive welding, friction stir welding, linear friction welding, cold welding, nanojoining, thermal bonding, and nanoscale soldering. This paper reviews the findings in the literature up to now in this evolving field, specifically, the experimental details, and the advantages and disadvantages of the various types of welding methods that have been proposed. Moreover, it highlights the big prospect of the molecular dynamics simulation and future directions for further research in the joining process.
Keywords: Molecular Dynamics Simulation; Joining; Welding; Bonding.